Millionaires for the month eaudiobook - McAnulty, Stacy (Listening Library, 2020)
How would you spend five million dollars in 30 days? A billionaire's wallet, a bizarre challenge, and an unlikely friendship send two kids on a wild adventure. From the author of The Miscalculations of Lightning Girl . Felix Rannells and Benji Porter were never supposed to be field-trip partners. Felix is a rule follower. Benji is a rule bender. They're not friends. And they don't have anything to talk about. Until . . . They find a wallet. A wallet that belongs to tech billionaire Laura Friendly. They're totally going to return it-but not before Benji "borrows" twenty dollars to buy hot dogs. Because twenty dollars is like a penny to a billionaire, right? But a penny has value. A penny doubled every day for thirty days is $5,368,709.12! So that's exactly how much money Laura Friendly challenges Felix and Benji to spend. They have thirty days. They can't tell anyone. And there are LOTS of other rules. But if they succeed, they each get ten million dollars to spend however they want. Challenge accepted! They rent cool cars, go to Disney World, buy pizza for the whole school-and that's just the beginning! But money can't buy everything or fix every problem. And spending it isn't always as easy and fun as they thought it would be. . . . As smart as it is entertaining, Millionaires for the Month is a thought-provoking story about friendship, privilege, and the value of a penny.